A Case Study Utilizing Multi-Method on The Implementation and Sustainability of Face-to-Face Classes in Magsaysay Districts, Division of Misamis Oriental, Philippines - Socaoco, Analiza Bernados (JPAIR Multidisciplinary Research, 2024)
In the wake of the COVID-19 outbreak, this case study examines the adoption and viability of in-person instruction in the Magsaysay districts of Misamis Oriental, Philippines. It fills in the knowledge gap about the unique customs and difficulties associated with the return of in-person instruction in rural areas. A mixed-methods approach was used in the study, incorporating focus group talks with school administrators and surveys. The results show that the district’s schools have successfully included in-person instruction by following health regulations, implementing blended learning, working with stakeholders, and implementing corrective measures. However, difficulties have been observed, including learning loss and behavioral problems in students. In order to solve these issues and guarantee the district’s continued capacity to provide in-person instruction, the study’s conclusion suggests an improved learning continuity plan. Policymakers and educators working in similar rural environments can greatly benefit from this research’s insightful observations, which emphasize the significance of customized approaches and continuous support for successful and long-lasting in-person instruction.